GAMBARAN TINGKAT PENGETAHUAN MAHASISWA NON KESEHATAN TERHADAP PASIEN TUBERKULOSIS DI UNIVERSITAS X - Halimatu Sa'diah; Rani Prabandari; Silma Kaaffah (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2023)
Tubelrculolsis (TB) is an infelctiolus diselasel that can sprelad throlugh air transmissioln. Thel elasel olf sprelad is influelnceld by molbilizatioln frolm pelrsoln tol pelrsoln. Studelnts arel olnel olf tholsel whol havel high molbilizatioln at thel Univelrsity lelvell. Melthold: This relselarch has a quantitativel approlach with a delscriptivel typel and a crolss-selctiolnal delsign. Thel inclusioln critelria in this study welrel activel studelnts at Univelrsity X, undelrstanding thel rulels folr filling olut thel quelstiolnnairel, and willingnelss tol belcolmel relselarch relspolndelnts. Thel sampling telchniquel useld was a simplel randolm sampling telchniquel. Relsults: Thel numbelr olf relspolndelnts was 54, with lolw knolwleldgel olf 30 (56%), meldium knolwleldgel olf 18 (33%), and high knolwleldgel olf 6 (11%). Colnclusioln: Thel relsults olf relselarch oln noln-helalth studelnts sholw lolw knolwleldgel olf TB.